Comparison of Intralesional Sodium Stibogluconate versus Intralesional Meglumine Antimoniate for the Treatment of Leishmania major Cutaneous Leishmaniasis - Michal Solomon; Ayelet Ollech; Felix Pavlotsky; Aviv Barzilai; Eli Schwartz; Sharon Baum; Nadav Astman (Medical Journals Sweden, 2024)
Israel is endemic for Old-World cutaneous leishmaniasis. The most common species is Leishmania major. However, the available treatment options are limited. This study's objective was to compare the authors' experience with different antimony intralesional treatments of Leishmania major cutaneous leishmaniasis. A retrospective evaluation was undertaken for cases of Leishmania major cutaneous leishmaniasis treated by pentavalent antimony in a university-affiliated medical centre in Israel. The previous treatment of intralesional sodium stibogluconate (Pentostam®) was compared with the current treatment of meglumine antimoniate (Glucantime®). One hundred cases of cutaneous leishmaniasis were treated during the study period, of whom 33 were treated with intralesional sodium stibogluconate and 67 were treated with intralesional meglumine antimoniate. The patients were 78 males and 22 females, mean age 24 (range 10-67) and there was a total of 354 skin lesions. Within 3 months from treatment, 91% (30/33) of the intralesional sodium stibogluconate group and 88% (59/67) of the intralesional meglumine antimoniate group had complete healing of the cutaneous lesions after an average of 3 treatment cycles (non-statistically significant). In conclusion, the 2 different medications have the same efficacy and safety for treating cutaneous leishmaniasis. Pentavalent antimoniate intralesional infiltration treatment is safe, effective, and well tolerated with minimal side effects for Old-World cutaneous leishmaniasis.